Implementasi Akuntansi Dana Desa di Desa Telukbango Kecamatan Batujaya Kabupaten Karawang - Ramadhan, Ziyadu; Harahap, Muhammad Nasim (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Village fund accounting is the process of recording the entry and exit of village finances in accordance with the Village Accounting Standards (SAPDesa) in the use of village fund budget allocations. The object of this research is located in Telukbango Village, Batujaya District, Kab. Karawang. The research method used is descriptive qualitative with the data used are primary data and supporting primary data. The results of the study, the financial system used by the village in preparing financial reports using Siskeudes and using a cash basis, Telukbango Village also uses Village Fund Accounting in the process of recording village financial statements consisting of Cash Books, Bank Books, Tax Books, APBDesa and Budget Realization Reports. , so that with the five reports, Telukbango Village is in the process of recording financial statements in accordance with the SAPDesa which contains transparency and accountability.